South America amid hegemonic narratives of critical minerals and the corporate energy transition - Guerrero, Ana Lia (Geografares, 2026)
From a critical South American perspective, this article analyzes how global actors contest and control hegemonic narratives about critical minerals and the so-called Corporate Energy Transition. Using an exploratory, mixed-methods approach, this study examines the geopolitical dimensions of these minerals in the global energy transition. The methodology draws on international organization reports, a comprehensive literature review, and my previous research. Results demonstrate that the corporate energy transition reproduces a framework of “green neocolonialism” under the guise of decarbonization. This process shifts structural dependence from fossil fuels to a multi-dependency on critical minerals, thereby deepening neo-extractivism across the Global South. In this context, I argue that South America faces the urgent challenge of redefining how its strategic resources are used and controlled. The region must overcome its subordinate global position and realign the energy transition with its own sovereign development priorities.